NAT2 gene polymorphisms and endometriosis risk: A PRISMA-compliant meta-analysis. - Zhangming Wei; Mengmeng Zhang; Xinyue Zhang; Mingyu Yi; Xiaomeng Xia; Xiaoling Fang (PLoS ONE)
Objective Endometriosis is a common chronic, gynecological disease. Despite many studies on the role of N-acetyltransferase 2 (NAT2) in endometriosis, its clinical significance is unclear. In this study, associations between NAT2 phenotypes as well as single nucleotide polymorphisms (SNPs) within NAT2 (i.e. rs1799929, rs1799930, rs1208, and rs1799931) and endometriosis risk were evaluated using a meta-analysis approach. Methods Embase, PubMed, ClinicalTrials.gov, CNKI (China National Knowledge Infrastructure), Wanfang databases, Cochrane Library for clinical trials, and Web of Science were searched to identify relevant articles. ORs (odds ratios) and 95% CIs (95% confidence intervals) were used to estimate the associations between NAT2 polymorphisms and endometriosis risk. Heterogeneity among included studies was also assessed. In addition, a subgroup analysis of NAT2 phenotypes and endometriosis risk based on ethnicity was performed. Results Nine case-control studies met the inclusion criteria. The odds ratio was 2.30 (95% CI: 1.61-3.28) for the NAT2 slow acetylation phenotype versus the intermediate + fast acetylation phenotype in the Asian population. These results suggest that Asian individuals with the NAT2 slow acetylation phenotype have a 130% increased risk of endometriosis. A significant association was also found for rs1799930 (OR = 0.74; 95% CI, 0.59-0.92), suggesting that individuals with this mutant genotype have a 26% decreased risk of endometriosis. Conclusions The rs1799930 mutant genotypes are associated with a decreased risk of endometriosis. No statistically significant associations were found between rs1799931, rs1208, or rs1799929 and endometriosis. Based on a subgroup analysis based on ethnicity, the NAT2 slow acetylation phenotype was found to increase the risk of endometriosis in Asians. No statistically significant associations were found between the NAT2 slow acetylation phenotype and endometriosis risk in Caucasians. Accordingly, NAT2 phenotypes and SNPs are potential biomarkers for the diagnosis and treatment of endometriosis.